Perceptions of Information Technology Governance Maturity Within Public Organizations: A Georgia Perspective - Watson, William Todd (My University, 2014)
As organizations become increasingly dependent upon information technology to provide critical business operations, more emphasis is placed upon the degree to which the technology function coordinates with organizational strategy. The effort to maintain control over a highly dynamic segment of the organization is considerable, requiring a continuous cycle of examination and correction. While iterative processes are beneficial to rudimentary business alignment efforts, in isolation they typically result in only modest improvements within the information technology function. A more compelling mechanism, therefore, is a management-driven program to improve oversight. In the private sector, increased levels of information technology governance have been positively correlated to profitability. However, in the public sector in general and in state governments in particular, few studies have been conducted to measure the relative maturity levels of governance in the information technology function. Benefits similar to those in the private sector are expected in the public sphere as information technology governance maturity increases by improving effectiveness and efficiency in the delivery of government services. In this exploratory study, the researcher surveyed organization executives and information technology managers across a number of state and county agencies in Georgia to gather and measure perceptions of governance maturity over the information technology function. The results of the study have several important implications for executives and policy makers who seek to improve organizational effectiveness.
Chapter I: INTRODUCTION 1 -- Organizational Governance Informing Information Technology Governance 4 -- Defining IT Governance 6 -- IT Governance Principles 8 -- IT Governance Goals 11 -- Public Sector Governance 12 -- Study Significance 16 -- Research Questions 16 -- Organization of the Research 18 -- Chapter II: REVIEW OF LITERATURE 20 -- Organizational Governance as an Archetype 20 -- Historical IT Governance 25 -- The Age of Governance 33 -- IT Governance as Public Policy 35 -- Georgia Public Policy 36 -- Governance Practices 36 -- When IT Governance Fails 39 -- Governance Processes, Mechanisms, and Tools 41 -- Chapter III: METHODOLOGY 51 -- Rationale for Using a Survey 52 -- Target Population and Data Collection Instrument 53 -- Analytical Methods 58 -- Research Considerations 60 -- Chapter IV: RESULTS 62 -- Reliability and Validity 63 -- Instrument Reliability 64 -- Instrument Validity 65 -- Population and Survey Responses 66 -- Analysis of Hypotheses 77 -- Chapter V: DISCUSSION 86 -- Significant Findings 86 -- Consideration of the Findings in Light of Existing Research 87 -- Implications of This Study 88 -- Limitations of This Study 89 -- Recommendations for Further Research 90 -- Conclusion 91 -- REFERENCES 92 -- APPENDIX A: Survey Instrument 107 -- APPENDIX B: Email Invitation to Participate 117 -- APPENDIX C: Agencies Invited to Participate 119 -- APPENDIX D: Institutional Research Board Protocol Exemption Report 127 -- APPENDIX E: Kaiser-Meyer-Olkin and Bartlett’s Test by Construct 129 -- APPENDIX F: Cronbach Alpha for Each Construct 132
Keywords: Public Administration; Governance; Information Technology; Georgia; Management